Eye Tracking the Feedback Assigned to Undergraduate Students in a Digital Assessment Game - Cutumisu, Maria; Turgeon, Krystle-Lee; Saiyera, Tasbire; Chuong, Steven; González Esparza, Lydia Marion; MacDonald, Rob; Kokhan, Vasyl (Frontiers in Psychology, 2019)
High-quality feedback exerts a crucial influence on learning new skills and it is one of the most common psychological interventions. However, knowing how to deliver feedback effectively is challenging for educators in both traditional and online classroom environments. This study uses psychophysiological methodology to investigate attention allocation to different feedback valences (i.e., positive and negative feedback), as the eye tracker provides accurate information about individuals’ locus of attention when they process feedback. We collected learning analytics via a behavioral assessment game and eye-movement measures via an eye tracker to infer undergraduate students’ cognitive processing of feedback that is assigned to them after completing a task. The eye movements of n = 24 undergraduates at a North American university were tracked by the EyeLink 1000 Plus eye tracker while they played Posterlet, a digital game-based assessment. In Posterlet, students designed three posters and received critical (negative) or confirmatory (positive) feedback from virtual characters in the game after completing each poster. Analyses showed that students attended to critical feedback more than to confirmatory feedback, as measured by the time spent on feedback in total, per word, and per letter, and by the amount of feedback revisits. The study summarizes the eye movement record on critical and confirmatory feedback, respectively. Implications of this research include enhancing our understanding of the differential temporal cognitive processing of feedback valences that may ultimately improve the delivery of feedback.